THE ARTISTIC WORLD OF LERMONTOV (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the novel “Hero of Our Time” M.Yu. Lermontov said: “The history of the human soul... is perhaps more curious and useful than the history of an entire People.” Not only Lermontov thought so, but also the whole generation of people of the 1830s, to which he belonged. They contrasted the energy of political action that inspired the generation of Decembrists with the energy of self-knowledge. At the same time, “The History of the Human Soul” was in no way opposed to the “history of the people.”